Workers with Disabilities and the Challenges of Creating an Inclusive Work Environment - E. A. Tomilova; A. Vvedensky; Yu. G. Egiazarov (Здоровье мегаполиса, 2024)
Introduction. Creating a workplace for workers with disabilities is a difficult task that requires considering a variety of factors. Many workplaces are not equipped with the necessary devices, such as height-adjustable tables, office chairs for disabled, or wheelchair lifts. Also, buildings may lack wheelchair ramps, elevators or wide doorways, which makes it difficult for people with limited mobility to access the workplace. These and many other factors significantly limit the possibilities of professional integration of persons with disabilities.The purpose of this work was to identify the main challenges of creating an inclusive working environment in order to increase the employment rates of workers with disabilities. In this research, an analysis of Russian and foreign literature was carried out.Materials and methods. The issues of the employment of workers with disabilities and the creation of an inclusive working environment were considered on the basis of a content analysis of scientific, review, and expert literature published both in scientific peer-reviewed publications and on the Internet. Papers by Russian and foreign authors, analytical data from national statistical agencies, and materials from government and corporate programs aimed at integrating persons with disabilities into social and professional life were studied.Results. Discussions on disability in the workplace have been extremely limited for a long time. However, statistics show that 5–8% of the working-age population have health problems that limit their ability to carry out professional activities. The workplace should be accessible to all employees, whether for routine work or emergency evacuation. Effective use of international experience as well as continuous improvement of inclusive practices will help to create more accessible and fair working conditions for all.